Social networks and member participation in cooperative governance. Issue 2 (6th August 2020) - Morfi, Chrysoula; Nilsson, Jerker; Hakelius, Karin; Karantininis, Kostas
Abstract: This study explored the relations between the farmer‐members' social networks and their interest in cooperative governance, specifically their willingness to be elected representatives. Several researchers assert that member interest in cooperative governance is related to social factors. The empirical basis consists of surveys of random samples of Swedish farmers conducted in 1993, 2003, and 2013. The results indicate a strong relationship between the social networks and the farmers' propensity to participate in cooperative governance. This relationship has persisted even though the investigated 20‐year period was very turbulent for Swedish agriculture. Over time, members have become more willing to be elected when they receive backing from their social networks, with personal networks being more important than professional networks. The professional networks are related only to the level of aspiration and not actual participation in governance. [EconLit Citations: D73, P13, Q13].